(untitled) (Bulletin of Armenian Libraries, 2024)
From 1672 to 1976 in Toronto the AYF “Simon Zavarian” chapter published the “Ardzagank” (Echo) monthly newspaper. The 58 issues were presented in 48 volumes: 8 volumes had two issues and one had 3 issues. Many exceptional articles were published in this monthly, which can still interest not only the readers but also the specialists dealing with issues of the Armenian Diaspora and the press. The rich material presented in this monthly is the diary of five years of the lives of Armenians in Toronto.